ACCESS TO EDUCATION AS A PROCESS OF RESOCIALIZATION OF YOUTH OFFENDERS: : A BIBLIOGRAPHIC REVIEW - Karla Barbosa de Freitas, Vanilma (Revista Gênero e Interdisciplinaridade, 2022)
Access to education for criminal minors who are in the process of resocialization is a subject that brings many discussions, but which still remains an obstacle in Brazilian education. Thus, the objective of this work is to understand how the process of access to education of these child offenders occurs in the socio-educational units and thus be able to analyze, through literature, the role of the State as well as of society itself. Thus, the work is a bibliographic review of the literature, using sources such as Scielo, google academic, laws and ordinances so that they can support the research and respond to the objectives concisely and effectively. Therefore, it was possible to perceive a certain difficulty in accepting the population with the young repeat offender of the crime committed, in addition to a difficulty in assisting the State to ensure a socioeconomic, psychological and educational support for this individual, clearly combining education as one of the foundations for the change of the individual. It is concluded that there is a need for the creation of effective public policies that meet this problem and a popular education that can broaden the understanding of the social body for the issue and that consequently breaks the stigmas ingrained in society in relation to the young offender.